Ribbon like appearance of the midsubstance fibres of the anterior cruciate ligament close to its femoral insertion site: a cadaveric study including 111 knees - Śmigielski, Robert; Zdanowicz, Urszula; Drwięga, Michał; Ciszek, Bogdan; Ciszkowska-Łysoń, Beata; Siebold, Rainer (Knee surgery, sports traumatology, arthroscopy, 2015)
Recently, the configuration of the anterior cruciate ligament (ACL) from its direct femoral insertion to midsubstance was found to be flat. This might have an important impact for anatomical ACL reconstruction. The purpose of this anatomical study was to evaluate the macroscopic appearance of the ACL from femoral to midsubstance.
Published online: 28 June 2014
Gesehen am 18.06.2020